AVOCADO LEAF AND FRUIT EXTRACT (PERSEA AMERICANA MILL) AS A FEED ADDITIVE FOR NILE TILAPIA (OREOCHROMIS SP.) - Deni Aulia; Dewi Virgiastuti Jarir; Isnainisa Woro Charity; Maqzanil Asywaq; Nunung Sabariyah; Umidayati Umidayati; Artin Indrayati (Universitas Mataram, 2024)
Nile tilapia (Oreochromis sp.) is one of the freshwater fish highly favored by fish farmers in Indonesia. The use of feed additives in fish diets to accelerate growth and enhance immunity has been widely practiced. Avocado is a natural plant known for its beneficial chemical compounds. This study aims to investigate the potential of avocado fruit and leaf extracts as feed additives for Nile tilapia. The Nile tilapia, with an average weight of 2.0 g/fish, were reared in 21 aquariums at a density of 16 fish/aquarium for 30 days. Avocado leaf and fruit extracts were mixed into the feed before being given to the fish. The study included seven treatments: avocado leaf extract at 5%, 10%, and 20% (DA5, DA10, and DA20), avocado fruit extract at 5%, 10%, and 20% (BA5, BA10, and BA20), and a control group without treatment (C). The final fish weight, weight gain, specific growth rate, and survival rate of Nile tilapia with avocado leaf and fruit extract treatments were higher compared to the control group. Conversely, the condition factor of fish without treatment was higher compared to those with treatments. Avocado fruit extract showed a more beneficial effect compared to avocado leaf extract. The use of higher doses of extracts demonstrated a better positive impact on Nile tilapia. Avocado fruit extract at a dose of 20% showed the best results for application in aquaculture activities.